Effects of public expenditures on agriculture at subnational levels on households’ welfare and economic resilience in Nigeria - Takeshima, Hiroyuki; Balana, Bedru; Smart, Jenny; Edeh, Hyacinth O.; Oyeyemi, Motunrayo; Andam, Kwaw S. (International Food Policy Research Institute, 2020)
Agricultural development has long been considered an important driver of overall economic development in developing countries such as Nigeria. Whether increasing public expenditures on agriculture (PEA) can directly improve broad dimensions of household well-being has continued to be debated. In addition, there has been growing interest in the economic flexibility of households to switch between nonfarm and farming activities. Such flexibility can potentially enhance the resilience of households to shocks like the COVID-19 pandemic in today’s rapidly changing socioeconomic environments. Direct evidence of the impact of PEA on broad development outcomes is also important in informing regional initiatives aiming to use PEA as an instrument for overall food security enhancement and poverty reduction in Africa. Using state- and local government area (LGA)-level PEA figures and household data in Nigeria, this study aims to provide initial evidence at the household level in Nigeria. The findings suggest that greater PEA shares have positive effects on various development outcomes at the household level, including consumption, poverty reduction, nonfarm capital investments, and household dietary diversity. The findings also suggest that greater PEA shares are likely to help farm households enhance their economic flexibility. These findings are consistent with the hypotheses of positive linkages between PEA and agricultural outcomes, and linkages between agricultural and nonagricultural outcomes, often advocated in the literature. PEA should be increased by increasing its share of total public expenditures through conscious efforts to reallocate existing resources, rather than trying to increase it by increasing the overall size of public expenditures. Furthermore, it remains important to identify the appropriate sources (for example, spending by LGA or state) and types of PEA (for example, recurrent or capital spending) for particular development outcomes.